FWCP (FIBERGLASS WHITE CARBON POWDER) APPLICATION AS A STREETFIGHTER MOTORCYCLE TANK MATERIAL - Della Chintya Ananda Filly; Rahmawan D. Prasetya; Nor Jayadi (Ide dan Dialog Desain Indonesia (Idealog), 2022)
: Today's society views motorbikes as no longer just a means of transportation, but also as part of their lifestyle. Not only for established groups, but also young people, they began to modify their motorcycles to look more beautiful or just follow the trends and times that are developing in the world of custom motorcycles. In addition to the aesthetics, motorcycle modification also takes into account the strength of the motorcycle variety products used. Many variations of motorcycle spare parts today do not pay attention to the life and durability of the spare parts themselves including the crucial part. The crucial part of a motorcycle is the motorcycle tank. Motorcycle tanks with metal or iron plates that are widely circulated in the market are susceptible to rust corrosion and also dents due to impact. The design of a custom motorcycle tank with fiberglass white carbon powder material provides convenience to custom motorcycle users in the maintenance of their tanks. With this fiberglass white carbon powder material, motorcycle tanks will be easier to maintain because they do not cause rust and can also withstand collisions with certain forces. Key words: motorcycle tank, fibreglass white carbon powder, custom motorcycle, corrosi